Biosynthesis of novel Ag@Cu alloy NPs for enhancement of methylene blue photocatalytic activity and antibacterial activity. (11th October 2019) - Kushwah, Mamta; Gaur, M S; Berlina, Anna N; Arora, Kavita
Abstract: We report the biosynthesis of Ag@Cu alloy nanoparticles (NPs) using phytochemicals as a reducing and capping agent. UV-Vis spectra shows the peak corresponding to Ag and Cu, which confirm the formation of alloy nanoparticles. The structure and morphology were measured by High Resolution-Transmission Electron Microscopy (HR-TEM), line diagram, x-ray diffraction (XRD), Fourier Transform Infrared spectroscopy and Zeta potential. The Ag@Cu alloy nanoparticles shows fast photocatalysis of Methylene Blue (MB) and antibacterial against Escherichia coli and Staphylococcus aureus at low concentration of alloy nanoparticles with more efficacies against Gram-negative bacteria. The enhancement of photocatalytic and antibacterial properties of Ag@Cu alloy nanoparticle may be due to high surface energy was investigated.